2020
DOI: 10.3390/microorganisms8111811
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Metatranscriptomics to Define Human and Microbial Functional Alterations Associated with Severe Obesity: A Pilot Study

Abstract: Obesity is a multifactorial disorder, and the gut microbiome has been suggested to contribute to its onset. In order to better clarify the role of the microbiome in obesity, we evaluated the metatranscriptome in duodenal biopsies from a cohort of 23 adult severely obese and lean control subjects using next generation sequencing. Our aim was to provide a general picture of the duodenal metatranscriptome associated with severe obesity. We found altered expressions of human and microbial genes in the obese compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 83 publications
(71 reference statements)
1
18
0
Order By: Relevance
“…Knowing that the metabolic activities of certain microbes could be suppressed by antagonists and so may not be actively involved in a given condition (phenotype), capturing such bacteria due to their sheer presence may give a false positive association. This is supported by studies that have reported that taxonomic abundance does not correspond to transcriptional activities [ 25 , 26 , 27 ]. The library construction, assembly, and reference databases of metagenomics for annotation employ biases that are difficult to understand [ 21 ].…”
Section: Omic Techniques In Gut Microbiome Studiessupporting
confidence: 68%
See 1 more Smart Citation
“…Knowing that the metabolic activities of certain microbes could be suppressed by antagonists and so may not be actively involved in a given condition (phenotype), capturing such bacteria due to their sheer presence may give a false positive association. This is supported by studies that have reported that taxonomic abundance does not correspond to transcriptional activities [ 25 , 26 , 27 ]. The library construction, assembly, and reference databases of metagenomics for annotation employ biases that are difficult to understand [ 21 ].…”
Section: Omic Techniques In Gut Microbiome Studiessupporting
confidence: 68%
“…For this reason, analyzing the mRNA produced by a microbe at a given time would be a better way to predict the metabolic activities and potential function(s) of the organism rather than making predictions based on its mere presence. Using metatranscriptomics, Granata et al [ 25 ] showed that carbohydrate, amino acid, and nucleotide metabolism are severely impaired in the duodenal microbiota of obese patients when compared to non-obese patients. Though the analytical technique is biased towards organisms with higher transcriptional rates, assigning mRNA reads to taxa could unveil critical functions contributed by keystone taxa.…”
Section: Omic Techniques In Gut Microbiome Studiesmentioning
confidence: 99%
“…Shotgun sequencing profiles may present information about the potential function(s) of an entire microbial community at the gene level based on databases of microbial genomes with known sequences, yet the information yielded by this method may not accurately represent what is happening in the gut at a given time (Emerson et al, 2017). This is supported by studies of taxonomic abundance that do not correspond to transcriptional activities (Abu-Ali et al, 2018;Jia et al, 2019;Granata et al, 2020). Utilizing this method, distinct meibum microbial communities were identified in patients with meibomian gland dysfunction and in healthy controls, indicating different immune evasive virulence of the meibum microbiota (Zhao et al, 2020).…”
Section: Metagenomicsmentioning
confidence: 99%
“…The same bacterial species has also been reported to fortify gut barrier functions by modulating mucin production in the gut, which may eventually prevent gut mucosal inflammation ( Graziani et al., 2016 ; Luissint et al., 2016 ). Using metatranscriptomics, Granata et al. (2020) showed that carbohydrate, amino acid, and nucleotide metabolism are severely impaired in the duodenal microbiota of obese patients compared to nonobese patients.…”
Section: Influences Of the Gut Microbiome And Analysis Approachesmentioning
confidence: 99%
“…Microbes play important roles in obesity. Previously, our group investigated the duodenal metatranscriptome in human obese and lean subjects, highlighting an obese-associated gut dysbiosis and human and bacterial genes both contributing to relevant dysfunctions in important metabolic pathways [ 17 , 18 ]. Regarding CRC alterations until now reported in the gut microbiota community or in single bacterial species in association with the tumor [ 19 ], in presence/absence of various risk factors among which increased adiposity, they have been mostly studied in murine models and/or in human fecal samples, but the human mucosal colon microbiome has still scarcely been investigated [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%